Prospective Clinical Trial of (18)F-Fluciclovine PET/CT for Determining the Response to Neoadjuvant Therapy in Invasive Ductal and Invasive Lobular Breast Cancers - Ulaner, Gary A. (J Nucl Med, 2017)
(18)F-labeled 1-amino-3-fluorocyclobutane-1-carboxylic acid ((18)F-fluciclovine) is a leucine analog radiotracer that depicts amino acid transport into cells. (18)F-fluciclovine PET/CT visualizes malignancy, including prostate cancer, invasive ductal breast cancer, and invasive lobular breast cancer. Whether changes in (18)F-fluciclovine avidity reflect changes in tumor burden resulting from treatment has not been shown. In this prospective clinical trial (clinical trials.gov: NCT01864083), changes in (18)F-fluciclovine avidity after neoadjuvant therapy were compared to breast cancer therapy response, as determined by residual tumor burden on pathology, were evaluated. Methods: Twenty-four women with a new diagnosis of locally advanced invasive ductal breast cancer (n = 18) or invasive lobular breast cancer (n = 6) underwent (18)F-fluciclovine PET/CT before and after the completion of neoadjuvant systemic therapy. SUV(max), SUV(mean), metabolic tumor volume, and total lesion avidity were obtained for the primary breast tumor, axillary lymph nodes, and extraaxillary lymph nodes on each examination and corrected for background (18)F-fluciclovine avidity. The relationship between changes in (18)F-fluciclovine avidity and the percentage of reduction of tumor on pathology was assessed with the Spearman rank correlation. Results: The median decrease in the corrected SUV(max) of the primary breast lesions was 99% (range, 33%–100%). The median reduction of tumor on pathology was 92% (range, 10%–100%). Changes in (18)F-fluciclovine avidity were strongly correlated with the percentage of reduction of tumor on pathology (Spearman ρ, 0.79; 95% CI, 0.56–0.90; P < 0.001). Conclusion: Changes in (18)F-fluciclovine avidity strongly correlated with the tumor response on pathology in this pilot study.